Exosome Derived from ADSCs Attenuates Ultraviolet B‐mediated Photoaging in Human Dermal Fibroblasts. (21st January 2021) - Gao, Wei; Wang, Xiu; Si, Yue; Pang, Jinlong; Liu, Hao; Li, Shanshan; Ding, Qi; Wang, Yushuai
Abstract: Stem cell therapies have attracted a lot of attention in the fields of dermatological and esthetic medicine. The paracrine action of stem cells is deemed to play a crucial role in skin treatments. Many reports have demonstrated the beneficial effects of conditioned medium (CM) derived from ADSCs on skin photoaging. However, few reports have presented the application of exosome (Exo) derived from ADSCs in the treatment of photoaging. To clarify the effects of Exo, we collected Exo from the CM of ADSCs and the photoprotective effects of Exo, as well as those of the CM with and without Exo, were investigated by detecting the intracellular ROS, DNA damage and some photoaging‐associated signal pathways on UVB‐treated human dermal fibroblasts. The results showed that Exo had significant efficiency in preventing photoaging, and it could inhibit UVB‐induced cellular DNA damage, overexpression of ROS and MMP‐1 via regulating Nrf2 and MAPK/AP‐1 pathway. In addition, Exo could effectively activate the TGF‐β/Smad pathway to elevate the expression of procollagen type I. However, these photoprotective effects were weakened when Exo was removed from the CM. Taken together, the results suggested that Exo, a key component of paracrine activity, played an important role in the treatment of photoaging. Abstract : Paracrine action of stem cells has been reported to ameliorate signs of skin photoaging, but their antiphotoaging mechanism remains elusive. Here, we explored the anti‐photoaging effect of exosome (Exo) derived from adipose‐derived stem cells conditioned medium and its mechanism of action. Our results indicated that Exo inhibited UVB‐induced intracellular ROS accumulation, DNA damage, and reduces MAPK/AP‐1 pathway phosphorylation to block MMP‐1 secretion. In addition, Exo activates TGF‐β/Smad pathway to increase procollagen type I synthesis and facilitates Nrf2 and cytoprotective antioxidants expression.